FACTORS INFLUENCING EMPLOYEE PERFORMANCE FOR IMPROVING ORGANIZATIONAL EFFECTIVENESS AT PHNOM PENH WATER SUPPLY AUTHORITY - Chor, Menghout; Try, Sothearith; Long, Sovang (Srawung: Journal of Social Sciences and Humanities, 2025)
The purpose of this study was to determine the factors influencing employee performance for improving organizational effectiveness at the Phnom Penh Water Supply Authority (PPWSA). This study used a descriptive method to gather, analyze, interpret, and present the information, applying a quantitative approach. The target population was permanent employees from the PPWSA. The sample size of the study is 500 respondents. The Google Forms tool created the survey for data collection and distributed the link to respondents through Telegram. The study collected data using a closed-ended questionnaire and analyzed it using both descriptive and inferential statistics. Confirmatory factor analysis (CFA) is used to make sure the dimensions are reliable and valid, and structural equation modeling (SEM) is used to test the model and hypotheses. After running a SEM, the research result indicates that training and development and organizational development significantly influence employee performance, while leadership and performance appraisal do not. Moreover, the study found that organizational development significantly influences organizational effectiveness, while training and development do not. Furthermore, employee performance has a positive and significant effect on organizational effectiveness. The study concluded that this finding will be useful to the management of PPWSA and other water supply firms in terms of understanding and learning more about how those variables interact and affect employee performance in order to improve organizational effectiveness in the workplace.